Eco-destination loyalty: Role of perceived value and experience in framing destination attachment and equity with moderating role of destination memory - Mengkebayaer, M.; Nawaz, Muhammad Asim; Sajid, Muhammad Umar (Frontiers in Psychology, 2022)
This research article aims to evaluate the characteristics of ecotourism destination loyalty in light of destination attachment, destination equity framed by perceived value, and tourist experience. Thus, the attributes of ecotourism destination branding in formulating tourist loyalty are examined. The study is of significant importance for developing economies having natural tourist destinations. A total of 358 questionnaires were filled through wjx, and a SmartPLS-based structural equation modeling tool was used to analyze the data obtained from eco-tourists. The software is essential for complex structural models, including multiple indicators, and relationships. The empirical results exhibit that perceived value and tourist experience significantly contribute to destination loyalty and equity, eventually influencing tourist destination loyalty. Moreover, destination memory moderates the relationship between destination attachment, destination equity, and destination loyalty. Further, destination attachment and destination equity mediate the relationship between the perceived value, experience, and destination loyalty. Additionally, the study extends the tourist consumption theory to the ecotourism literature. Besides the theoretical contribution, the study makes a practical contribution to practitioners. For instance, perceived value is a prime contributor to tourist destination loyalty. In perceived value, the most important factor is good value for money. Such practical contribution will provide a pathway to the strategic formation of business.